2002
DOI: 10.2165/00002018-200225140-00005
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Feasibility of Using an Adverse Drug Reaction Preventability Scale in Clinical Practice

Abstract: These results emphasise that ADRs leading to hospitalisation are frequent, with one-third of them likely to be preventable. Moreover, the risk of ADRs mainly involved a small number of drugs. Our experience suggests that there is a need for further studies to validate the French standardised scale of preventability assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 15 publications
4
24
0
2
Order By: Relevance
“…It is possible that older people who suffer from more serious illness are more frequently hospitalized or referred to tertiary care units. Our finding that ADE-related ED visits more frequently affected the skin (34.21% of total events) and the gastrointestinal system (21.05%) is in agreement with a previous report [21]. The drugs involved were antibiotics, NSAIDs, and agents acting on the renin-angiotensin system.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is possible that older people who suffer from more serious illness are more frequently hospitalized or referred to tertiary care units. Our finding that ADE-related ED visits more frequently affected the skin (34.21% of total events) and the gastrointestinal system (21.05%) is in agreement with a previous report [21]. The drugs involved were antibiotics, NSAIDs, and agents acting on the renin-angiotensin system.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, recent findings have reported that one-third are likely preventable [21] and that about half could be avoided with greater prescription care [22].…”
Section: Introductionmentioning
confidence: 99%
“…Four (3%) articles mentioned assessing the validity of the preventability assessment (56,(61)(62)(63). In one (1%) article (62), an assessment method introduced by the authors was compared with a previously introduced method and the number of identified cases by the two methods was reported.…”
Section: Resultsmentioning
confidence: 99%
“…In one (1%) article (62), an assessment method introduced by the authors was compared with a previously introduced method and the number of identified cases by the two methods was reported. However, no sensitivity or specificity analysis or negative or positive predictive values were not reported.…”
Section: Resultsmentioning
confidence: 99%
“…Esto, teniendo presente reacciones adversas a medicamento confirmadas y validadas, significa que por cada RAM confirmada hay muchos más eventos adversos a medicamentos, hecho confirmado también por otros investigadores (30,31). Las RAM pueden causar incrementos significativos de la morbimortalidad de los pacientes, en especial aquellos hospitalizados.…”
Section: Discussionunclassified